BIODIVERSITY OF TASAR SILKWORM, BREADING PERFORMANCE, CONSERVATION, GENETICS ANALYSIS AND BIOMEDICAL APPLICATION. (International Journal of Food and Nutritional Sciences, 2023)
Silk is the most common rearing agro based industries world wise practicing and is not onlyvaluable this is ultimate and wonderful gift of the nature are produced by Sericigenous insectsbelonging families Bombycidae and Saturniidae of order Lepidoptera.